The measurement of kinetic variables in race walking - Hanley, B.; Drake, A.; Bissas, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to measure kinetic variables during race walking. Forty national and international race walkers walked either 5 km or 10 km at a pace equivalent to 105% of their season`s best time. Junior athletes walked 5 km, while senior athletes (mostly 20 km walkers) walked 10 km. Kinetic data were collected using a Gaitway treadmill (1000 Hz). Data were collected at the 2.5 km point. Men had longer step lengths than women and walked faster as a result. There was little difference in cadence. Average flight times for each group of athlete were approximately 0.04 s. Senior athletes showed more `typical` race walking vertical force patterns than the juniors; this may be linked to quantity of training experience and gait efficiency. Athletes are advised to develop muscular strength endurance to cope with loading rates upon initial contact.